The Murut Tahol Culture in Sabah: The Historical Journey and Challenges - Abd Hakim Mohad @ Mohamad Ramli; Sarjit S Gill; A. T. Talib; Puvaneswaran Kunasekaran (Canadian Center of Science and Education, 2024)
The Murut Tahol community is one of the few well conserved indigenous groups in Sabah. This community is known for being a community that has its own distinctive identity. Although they were ruled by various administrations like the British North Borneo Charted Company (BNBCC) since 1881 till 1941, the Japanese Ruling (1946-1962), the era of post-independence since 1963; they are still holding adamantly to their traditional culture. The arrival of religious influences like Christianity started since the 1950s also did not distance themselves with their community's culture. Therefore, this has proven the ability of the Murut Tahol community to ensure their traditional cultures are preserved. Research that has been done on the Murut Tahol community in Kampung Alutok, Ulu Tomani, shows that the community is making adaptations to its culture so that it can be on par with the religion they have adopted and that it is well-suited with the passing of time. Therefore, their culture has always been relevant to the time and conditions of their community. The interesting thing about this community is their ability to separate cultural landscape that cannot be changed with the cultural practices that can be flexible; subsequently making their own choices on the cultural aspect that needs to be preserved or otherwise.